The Effect of Human Resources Development on the Performance of State Civil Servants (ASN) - Martini Martini; Henson Enjein Manurung; Januar Ida Wibowati; Endang Rahayu (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
Natural Resource Development will provide benefits to state civil servants (ASN) at the Ministry of Religion of South Sumatra Province. Agencies will get benefits in the form of increasing performance, productivity, elasticity, and flexibility to adapt to an ever-changing environment. The purpose of this research is